A NUMERICAL MODEL STUDY OF FIELD WATER DYNAMICS IN THE TOP SOIL LAYER WHICH INVOLVE ROOT UPTAKE - Erari, Ishak S. (Prosiding Seminar Nasional MIPA, 2012)
AbstractTop soil is an important part of the soil to growing the crop because it is a medium to the root distribution and the available water. Vegetables as mustard greens, need water much more to their growing. The last years, long dry period has forced to using irrigation water efficiently. An experiment of the water dynamics to managing need crop water in the top soil was be conducted at clay loam from Bogor, West Java. This experiment of the water dynamics involved the water uptake rate by root of mustard greens (Brassica juncea). The root uptake rate was modeled as a fixed resistance network collaborating the macroscopic model and the microscopic model. The water dynamics equation was numerically solved by the control volume method. Simulation result of the root uptake model compared to the actual transpiration rate data revealed agreement until 18 days of age of the crop in the field. After 18 days, the model overestimates to the actual transpiration data. This was caused by the lisimeter used impermeable to the water. The numerical solution of the water dynamics derived by the control volume method revealed in agreement with the measured data. Distribution of the water in the top soil layer is influenced by the root length density